Social Practices of Regent Lilis' Victory in the 2024 Kebumen Regency Election: Case Study of Victory - Alya Meida Pristiani; Arief Affandi (PT Pro Panoramic Solution, 2026)
This study examines the phenomenon of Regent Lilis' victory in the 2024 Kebumen Regency election, which brought with it a number of challenges that could have hindered her victory. These challenges included her husband's negative background, who had been involved in a bribery case, issues of political dynasties, and stereotypes against women. The researchers used Pierre Bourdieu's Social Practice Theory and Knowledge-Power-Discourse Theory to analyze how social practices contributed to Lilis' victory in the 2024 regional election in Gombong District. The research method used in this study was qualitative with a case study approach. The results of this study show that the social practices used by Regent Lilis to win in Gombong Subdistrict were not much different from previous social practices used to win. The resources and capital owned by her husband, former Regent Yahya Fuad, continued to be maintained and strengthened by Regent Lilis. So, even though the domain was different, Regent Lilis was still able to win votes in Gombong Subdistrict just like her husband. In addition, the narrative